(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
The most common ways of milled asphalt re-use, what is formed during road topping repair is considered. The results of experimental studies of preparation technology features and physical and mechanical properties of recycled hot mix asphalt determination based on milled asphalt with plastic fiber addition that obtained from industrial waste is presented. Defined regulations correspondence obtained recycled hot mix asphalt and ways of their use in road construction is determined.